2015
DOI: 10.1152/physrev.00020.2014
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Calcium Channels

Abstract: Store-operated calcium channels (SOCs) are a major pathway for calcium signaling in virtually all metozoan cells and serve a wide variety of functions ranging from gene expression, motility, and secretion to tissue and organ development and the immune response. SOCs are activated by the depletion of Ca(2+) from the endoplasmic reticulum (ER), triggered physiologically through stimulation of a diverse set of surface receptors. Over 15 years after the first characterization of SOCs through electrophysiology, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
1,264
4
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 975 publications
(1,301 citation statements)
references
References 479 publications
(821 reference statements)
23
1,264
4
10
Order By: Relevance
“…
Ca 2+ release-activated Ca 2+ (CRAC) channels are prototypic store operated channels that are encoded by the Orai family of plasma membrane proteins and activated by depletion of Ca 2+ from the ER (Prakriya and Lewis, 2015). The ER protein STIM1 is best recognized for its function in sensing ER Ca 2+ depletion and, in response, activating CRAC channels in the plasma membrane.
…”
mentioning
confidence: 99%
“…
Ca 2+ release-activated Ca 2+ (CRAC) channels are prototypic store operated channels that are encoded by the Orai family of plasma membrane proteins and activated by depletion of Ca 2+ from the ER (Prakriya and Lewis, 2015). The ER protein STIM1 is best recognized for its function in sensing ER Ca 2+ depletion and, in response, activating CRAC channels in the plasma membrane.
…”
mentioning
confidence: 99%
“…STIM1 functions as an ER Ca 2+ sensor, and Orai1 is a pore subunit located on the plasma membrane 48. Although there exist arguments on whether TRPC1 is a component of SOCE channel,49 our recent results from human cardiac c‐Kit + progenitor cells13 support the notion that TRPC1 works together with Orai1 to form discrete STIM1‐gated SOCE channel, mediate distinct Ca 2+ signals and regulate specific cellular functions 50, 51, 52…”
Section: Discussionmentioning
confidence: 81%
“…[27][28][29] In this study, we found that mechanical stretch induced by nanoparticles, in this case QDs, elevated [Ca 2+ ] i in the Calu-3 epithelial cell layer and that this elevation was suppressed ] i signals in both excitable and nonexcitable cells is the family of storeoperated Ca 2+ channels, which responds to the reduction of ER intraluminal Ca 2+ entry. 30 The SOCE has been shown to play an important role in the ciliary beating and ion transport of airway epithelial cells. 11,26 Our study indicated that SOCE inhibitor BTP2 could inhibit the [Ca 2+ ] i increase in response to QD deposition in Calu-3 layer.…”
Section: Discussionmentioning
confidence: 99%